The Effect of the Fiber Bragg Grating model & Index modulation on the Spectral Characteristics of Fiber Bragg Grating - Mohammed, Zahraa (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Fiber Brag Grating FBG Works as a filter within a specific range to counteract the light whose wavelength is within the filter range and allows the light whose wavelength is outside the filter to pass through the carrier light-medium. In communications fiber-optic, the FBG is used to separate the optical signals. The Apodization techniques are used to get the optimum reflection spectrum. In this paper, two comparisons used dependent on the types of grating apodization& change index mode of FBG. The FBG equations for the uniform pattern and the Apodization pattern are, Gaussian Apodized FBG and Hyperbolic tangent (tan hyp) Apodized FBG are processed by the optigrating (4.2.2) software to achieve the maximum Reflectivity and Narrow bandwidth that reduces the effect of sidelobe, then change the index modulation of the fiber grating to find the relation between the maximum reflectivity, bandwidth, and sidelobe with index mode. Results are obtained and installed with graphs and tables.